SIgZ exhibited maternal transmission in embryonic development and played a prominent role in mucosal immune response of Megalabrama amblycephala. (July 2016) - Xia, Hu; Liu, Wanjing; Wu, Kang; Wang, Weimin; Zhang, Xuezhen
Abstract: IgZ is considered to be the last immunoglobulin discovered in vertebrate species. In this study, the structure of secreted form of blunt snout bream ( Megalabrama amblycephala ) IgZ (sIgZ) heavy chain gene is VH-Cζ1-Cζ2-Cζ3-Cζ4, in which Cζ4 provides the specificity to the IgZ isotype. The deduced amino acid sequence of sIgZ shows highest similarity with that of Ctenopharyngodon idella (79%). The ontogeny of sIgZ gene expression showed a V-shape change pattern: decreased initially from unfertilized egg stage to 16-cell embryos and increased significantly from blastula stage, which exhibited maternal transmission effects. Compared with the juvenile fish, sIgZ mRNA level was higher in head kidney, spleen, trunk kidney, liver, intestine and gill of adult fish. In both juvenile and adult fish, sIgZ mRNA was detected in intestine and gill. Aeromonas hydrophila challenge experiment showed that sIgZ transcription significantly increased in skin, gill and intestine, indicating a prominent mucosal immune response. The results of Western blot also verified the protein alterations of sIgZ in mucosal organs in M. amblycephal . Our studies indicate a prominent role of IgZ in mucosa-associated lymphoid tissue immunity and further support the specialized role of IgZ in teleost mucosal immune responses. Highlights: The structure of Megalabrama amblycephala sIgZ is VH-Cζ1-Cζ2-Cζ3-Cζ4. The Cζ4 provides the specificity to the IgZ isotype. The level of sIgZ mRNA increased significantly from blastula stage. The ontogeny of sIgZ gene expression exhibited maternal transmission. After Aeromonas hydrophila infection, sIgZ played a key role in mucosal immune response.